Combined impact of elevated C-reactive protein levels and dyslipidemia on stroke: a CHNS prospective cohort study - Lv, Meiru; Su, Chang; Huang, Feifei; Jia, Xiaofang; Zhang, Jiguo; Wang, Huijun; Wu, Xiaoyu; Zhou, Weiwei; Du, Wenwen (Frontiers in Public Health, 2024)
The objective of this study was to examine whether the combination of elevated levels of C-reactive protein (CRP) and dyslipidemia increased the risk of stroke among middle-aged and elderly individuals in China.This study utilized longitudinal data from the China Health and Nutrition Survey (CHNS) collected in 2009, 2015, and 2018. A total of 8,023 participants aged ≥40 years (3,595 males and 4,428 females) were included. The Generalized Estimating Equation (GEE) method was employed to examine the association between inflammation, dyslipidemia, their combined effects, and stroke in the Chinese population.Results: A total of 174 stroke events occurred during follow-up. Compared with those with normal CRP levels (CRP≤3mg/L) , the adjusted ORs and 95%CI were 2.13 (1.25, 3.64) for the female with elevated CRP level. Compared with those with non-dyslipidemia, the adjusted ORs and 95%CI were 1.56 (1.03, 2.37) for the individuals with high LDL cholesterol, 1.93 (1.12, 3.33) for the male with high LDL cholesterol. Compared with those with normal CRP levels and non-dyslipidemia, the adjusted ORs and 95%CI were 1.74 (1.08, 2.78) for the individuals with elevated CRP levels and dyslipidemia, 2.41 (1.29, 4.49) for the male with elevated CRP levels and dyslipidemia. People with the coexistence of elevated CRP levels and dyslipidemia had the highest risk of stroke among male.In females, higher levels of inflammation are associated with an increased incidence of stroke. In males, individuals with dyslipidemia characterized by high LDL cholesterol levels are more susceptible to stroke. In the general population, the joint effect of inflammation and dyslipidemia predisposes individuals to a higher risk of stroke, particularly among males.